2014
DOI: 10.3389/fphar.2014.00071
|View full text |Cite
|
Sign up to set email alerts
|

Erk5 is a mediator to TGFβ1-induced loss of phenotype and function in human podocytes

Abstract: Background: Podocytes are highly specialized cells integral to the normal functioning kidney, however, in diabetic nephropathy injury occurs leading to a compromised phenotype and podocyte dysfunction which critically produces podocyte loss with subsequent renal impairment. TGFβ1 holds a major role in the development of diabetic nephropathy. Erk5 is an atypical mitogen-activated protein (MAP) kinase involved in pathways modulating cell survival, proliferation, differentiation, and motility. Accordingly, the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…García-Hoz et al revealed that CCh induces the formation of Gαq/protein kinase C (PKC) ζ and MEK5 protein complexes to trigger ERK5 activation in mouse embryonic fibroblasts [ 35 ]. Badshah et al reported that TGF-β1 mediates ERK5 activation in human podocytes without the involvement of the small GTPase Ras [ 36 ]. In the present study, CCh and TGF-β1 induced ERK5 phosphorylation in lung fibroblasts, and BIX02189 attenuated CCh- or TGF-β1-induced gel contraction and α-SMA expression.…”
Section: Discussionmentioning
confidence: 99%
“…García-Hoz et al revealed that CCh induces the formation of Gαq/protein kinase C (PKC) ζ and MEK5 protein complexes to trigger ERK5 activation in mouse embryonic fibroblasts [ 35 ]. Badshah et al reported that TGF-β1 mediates ERK5 activation in human podocytes without the involvement of the small GTPase Ras [ 36 ]. In the present study, CCh and TGF-β1 induced ERK5 phosphorylation in lung fibroblasts, and BIX02189 attenuated CCh- or TGF-β1-induced gel contraction and α-SMA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of ERK5 increased adiposity with dysregulation in adipokines secretion, leptin resistance, and impaired glucose handling [116]. It has been identified that above effect of ERK5 in diabetic nephropathy is mediated by TGFβ1 induced phosphorylation of MEK5 without involvement of the MAP3K Ras [117]. There are no extensive studies on ERK3, ERK4 and ERK7, hence there is a need to study their role in insulin resistance.…”
Section: Role Of Erks In Glucose Metabolism and Insulin Resistancementioning
confidence: 99%
“…Among all signalling molecules, MAPKs are factors that are connected to different pathways. As a focus of this study, ERK5 can be activated through NGF and its receptor TrkA at the nerve terminal, or be activated through G‐CSF/G‐CSF receptor in the regulation of granulopoiesis, or be activated through TGF‐beta/TGF‐beta receptor in the control of function and survival of podocytes . However, the association of ERK5 with Hsp90 and Cdc37 super‐chaperone renders ERK5 a regulator of other signalling pathways that include Hsp90 or Cdc37 as involved molecules .…”
Section: Discussionmentioning
confidence: 99%